Topical effects of SCA® (Cryptomphalus aspersa secretion) associated with regenerative and antioxidant ingredients on aged skin: evaluation by confocal and clinical microscopy - Addor FA (Dove Medical Press, 2019)
Flavia Alvim Sant’Anna Addor Clinical Research Department, Medcin Pesquisa, Osasco, Sao Paulo, Brazil Purpose: This was an open-label, single-center clinical study to evaluate a topical association of SCA® (Cryptomphalus aspersa secretion) with regenerative and antioxidant ingredients, according to the type and area of the face, on the improvement of signs of skin aging.Patients and methods: One hundred and twenty female participants aged between 40 and 65 years, with facial aging complaints (presence of static, dynamics wrinkles, loss of elasticity, and skin firmness) were randomized into two groups according to the type of skin: normal–oily and normal–dry, and 40 participants were randomized for evaluation of the periocular area (with the presence of wrinkles, expression lines, and dark circles) with both types of skin. The groups received serum for normal–oily skin, a cream for normal–dry skin, and a cream for periocular and eyelid skin (eye area). All the participants were evaluated by a dermatologist and submitted to hydration evaluation by corneometry, elasticity and firmness measures complementarily, and images were collected in confocal reflectance microscopy.Results: Topical skin treatment with the association of SCA with antioxidant ingredients (green coffee oil, olive oil, ectoine, hyaluronic acid, and peptides) was able to promote significant clinical and subjective improvement of all signs of skin aging. This improvement was presented at the epidermal level, with improved hydration levels measured by corneometry and epidermal thickness, and at the dermal level, with improvement of the firmness and elasticity parameters, measured by cutometry, from 45 days of use.Conclusion: All the evaluated topical formulations seemed to be an effective alternative for the progressive treatment of signs of skin aging, since they demonstrate a real improvement of dermal–epidermal structure and function with high safety margin for long-term use. Keywords: skin aging, confocal microscopy, photoaging, collagen